UNDERSTANDING THE INFLUENCE OF HEDONIC MOTIVATION AND FEAR OF MISSING OUT (FoMO) ON ONLINE IMPULSE PURCHASE INTENTIONS OF DISCOUNTED PRODUCTS - Otilia-Elena PLATON (Challenges of the Knowledge Society)
In the fast-paced world of online commerce, understanding the psychological drivers behind consumers' impulse purchase intentions of discounted products is essential for businesses seeking to optimise their ecommerce strategies and drive sales. This article aims to synthesise key insights into the interplay between hedonic motivation, fear of missing out (FoMO) and other psychological factors influencing online impulse buying behavior. Hedonic motivation, driven by the pursuit of pleasure and enjoyment, plays a central role in shaping consumers' preferences, choices, and purchase decisions. When coupled with the fear of missing out (FoMO), characterised by the fear of being excluded from rewarding experiences or opportunities, hedonic motivation intensifies consumers' desire to act quickly and make impulsive purchases, particularly when presented with limited-time discounts or attractive offers. Discounted products, with their perceived value and scarcity, serve as potent triggers for impulsive buying behavior, as consumers strive to capitalise on the opportunity for pleasure and gratification while avoiding feelings of regret or exclusion. Factors such as social comparison, emotional triggers, and perceived risk further influence consumers' online impulse purchase intentions, driving them to seek validation, relief, or reassurance through their purchasing decisions. Businesses can leverage these insights to design targeted marketing strategies, personalised offers, and compelling shopping experiences that resonate with consumers' hedonic motivations and address their fears of missing out. By employing behavioral nudges, visual appeals, and social proof cues, businesses can create a sense of urgency, enhance perceived value, and mitigate perceived risk, ultimately driving impulse purchases and increasing conversion rates in the competitive digital marketplace. By considering the multifaceted impact of hedonic motivation, FoMO and other psychological factors on consumers' online impulse purchase intentions of discounted products, businesses can create engaging online shopping experiences that foster customer satisfaction, loyalty, and long-term success.